Effect of morphology on the biomechanics of contusion models of non-human primate spinal cord injury: a finite element study in a digital population - Numaira Obaid; Dexter L. Zamora; Cesar Jimenez-Gonzalez; Carolyn J. Sparrey (PLoS ONE, 2026)
Traumatic spinal cord injuries (SCIs) stem from mechanical events that translate external forces through the spinal column, damaging the spinal cord. Since tissue damage is related to the strain/stress it experiences, finite element models are being increasingly used to supplement pre-clinical models of animal SCI. Simulations; however, are often conducted in a single geometry, while morphological variability has been highlighted as having an important influence on biomechanical outcomes. We developed tissue scale finite element models of non-human primate spinal cord injury with different morphologies (N = 40) to assess the effect of morphology on biomechanical outcomes. Applying the same displacement to different digital subjects generated different peak forces, and the magnitude of these forces was related to subject morphology, specifically the area of cerebrospinal fluid (CSF) and the occlusion of the spinal canal by the spinal cord (SCO/SC), particularly in the mediolateral direction (SCOW/SCW). Despite the same loading (0.75 N preload and 4-mm displacement at 500 mm/s), different subjects experienced a wide range of impact forces (13–33 N) due to morphological differences. In pre-clinical experiments, this variability could lead to drastically different outcomes, ranging from no functional deficits at the lower end (13 N) to unintended contralateral contusions at the higher end (33 N), despite the intent to induce unilateral injury. Peak forces were statistically correlated with white matter sparing, which affects observed functional outcomes. We showed that both tissue-level and impact biomechanics are significantly affected by morphology, emphasizing the need to include diversity and morphological variability into computational models of spinal cord injury. This highlights that either impact parameters need to be adjusted for morphological variability or that animals should be pre-screened for cord/column morphology, which can be prohibitively expensive. Future work is needed to determine how to scale these impact parameters for different morphologies.